A New Species of the Genus Garra Hamilton, 1822 from the Chindwin Basin of Manipur, India (Teleostei: Cyprinidae: Labeoninae). (4th March 2012) - Shangningam, Bungdon; Vishwanath, Waikhom
Abstract : Garra namyaensis sp. nov., a new cyprinid fish, is described from the Chindwin River basin in Manipur, India. It is distinguished from its congeners in having a unique combination of the following characters: smoothly rounded snout tip with a prominent rostral lobe, chest and abdominal region with scales, dorsal fin with a black band near the posterior margin, and caudal fin with a distinct W-shaped black band.